Chinese expert consensus on the multidisciplinary management of pneumonitis associated with immune checkpoint inhibitor. Issue 23 (21st October 2022) - Wang, Wenxian; Wang, Qian; Xu, Chunwei; Li, Ziming; Song, Zhengbo; Zhang, Yongchang; Cai, Xiuyu; Zhang, Shirong; Lian, Bin; Li, Wen; Liu, Anwen; Zhan, Ping; et al.
Abstract: Immune checkpoint inhibitors (ICIs) have successfully treated a number of different types of cancer, which is of great significance for cancer treatment. With the widespread use of ICIs in clinical practice, the increasing checkpoint inhibitor pneumonia (CIP) will be a challenge to clinicians. To guide the diagnosis and treatment of CIP, we conducted in‐depth discussions based on the latest evidence, forming a consensus among Chinese experts on the multidisciplinary management of CIP. Abstract : Chinese expert consensus on the multidisciplinary management of pneumonitis associated with immune checkpoint inhibitor.